Pre-Burial Rites in Tutu in the Akuapem Traditional Area of Eastern Part of Ghana - Gyamerah, S. K. (University of Ghana, 2014)
This study was largely inspired by a desire to illustrate the uniqueness of the Amaneb[ rite, a pre-burial rite, of the people of Tutu in the Akuapem Traditional Area in the eastern part of Ghana, and shed light on the relevance for its continuous observance in contemporary Tutu society. The phenomenological approach was employed to guide the data collection. On the research field, the researcher employed interviews, participant observation and purposive sampling techniques to gather the required data. The researcher has employed Victor Turner’s famous theory of ‘Liminality’, to ground the discussion. Among other findings, the rite is seen as a mandatory liminal rite, which encompasses some aspects of religio-cultural beliefs and practices of the people of Tutu and that any attempt to modify or change it is met with strong resistance by the custodians of the community. The performance of the rites also revealed that their resistance was due to certain values cherished and revered by the people. Among them include the resolution of conflicts and seeming contradictions to bring reconciliation between the material and the spiritual, to initiate smooth transition of the deceased to ancestral home, to advocate the solidarity and communality of indigenous living for a common purpose and as a means to enforce the moral values of the community. It can be concluded that the continuous observance of this rite and similar indigenous practices of the AIR or its functional equivalent, in spite of the contemporary social change has entrenched itself and may never wholly disappear. Indigenous religious beliefs and practices will continue to manifest its resilience over the other religious traditions. However, there is the need to perform a study to find out among other issues the correlation between such indigenous religious beliefs and practices and the development of the indigenous societies.
Thesis (MPhil) - University of Ghana, 2014
Keywords: Pre-Burial Rites; Akuapem; Traditional Area; Eastern Part of Ghana